3’-R-Spiro[cycloalkyl-1(2), (hetaryl-3(4), 6’-[1,2,4]triazino[2,3-c] quinazoline]-2’(7’H)-2-оnes as a perspective class of compounds with actoprotective activity - Kolomoets, O. S.; Voskoboynik, О. Yu.; Nosulenko, I. S.; Kryvoshey, O. V.; Avramenko, A. I.; Berest, G. G.; Kovalenko, S. I.; Коломоєць, Олександра Сергіївна; Воскобойнік, Олексій Юрійович; Носуленко, Інна Степанівна; Кривошей, Оксана Вікторівна; Авраменко, Антоніна Іванівна; et al. (Zaporizhzhia state medical university, 2017)
Quinazolines and their derivatives are a perspective class of compounds with versatile biological activities. Their representatives are used in medical practice as sleeping, diuretic, antimicrobial and antitumor drugs. Continuing our search of perspective compounds with actprotective activity among azolo-(azino-)[c]quinazoline derivatives it was decided to combine the mentioned above heterocyclic system with carbocyclic or heterocyclic fragments in one molecule. Moreover, an affinity to melanocortin-4, nociceptin (NOP), adenosine, GABA and glutamine receptors among spiropiperidines, spiropiperidinoquinazolines, spiropiperidi notriazoloquinazolines, spiroindolinoquinazolines and others was found and as a rule they exhibit neuroprotective, neurotrophic, anti-inflammatory and other actions. Aim. The aim of the present work was the primary screening of actoprotective activity among novel 3’-R-spiro [cycloalkyl-1(2), (hetaryl-3(4), 6’)-[1,2,4]triazino[2,3-c]quinazoline]-2’(7’H)-2-ones, estimating of antiradical activity as the possible mechanism of actoprotection and the evaluation of perspectivity of further profound researches for high-active compounds. Materials and methods. Actprotective activity of perspective and unknown 3’-R-spiro[cycloalkyl-1(2), (hetaryl-3(4), 6’-[1,2,4] triazino[2,3-c]quinazoline]-2’(7’H)-2-ones was studied using the swimming test at the temperature 24–26 °C (normothermia) with additional load (10 % from the weight of experimental animal). The experiment was carried out on white Wistar rats and “Mildronate” was used as a reference drug. Results and discussion. It was found, that most of the tested compounds being intragastrically administrated increased the duration of experimental animals swimming in dose of 50 mg/kg in conditions of normothermia. Also, we found a number of high active compounds (1.6, 1.11, 1.12, 1.18, 1,19, 1.25), that were superior to the reference drug “Mildronate” by the level of actoprotection on 13.2–47.8 %. It was shown that there is no reliable dependence between actoprotective and antiradical activities among 3’-R-spiro[cycloalkyl-1(2), (hetaryl-3(4), 6’-[1,2,4]triazino[2,3-c]quinazoline]-2’(7’H)-2-ones. The analysis of “structure – activity” correlation showed that critical factors in revealing of high actprotective action is not only the size and nature of spirocycle of position 6, but also a substituent in position 3 of triazino[2,3-c]quinazoline system. The most active compounds 1.6, 1.11, 1.12, 1.18, 1.19 and 1.25 were recommended for further pharmacological studies. Хіназоліни та їхні похідні – перспективний клас сполук із різноманітною біологічною активністю, представники якого застосовуються в медичній практиці як снодійні, діуретичні, антимікробні, протипухлинні засоби. У продовження попередніх досліджень щодо пошуку перспективних сполук з актопротекторною активністю серед похідних азоло-(азино-)[c] хіназолінів цікавим було поєднання в одній молекулі карбоциклічних і гетероциклічних фрагментів. Ба більше, що серед спiропіперидинів, спіропіперидинохіназолінів, спіропіперидинотриазолохіназолінів, спіроіндолінохіназолінів виявлена аффінність до меланокортину-4, ноцицептинових (NOP), аденозинових, ГАМК- і глутамінових рецепторів, і вони, як правило, проявляють нейропротекторну, нейротрофічну, протизапальну та інші дії. Мета роботи – первинний скринінг 3’-R-спіро[циклоалкіл-1(2), (гетарил-3(4), 6’)-[1,2,4]триазино[2,3-c]хіназолін]-2’(7’H)-2- онів на актопротекторну активність, вивчення антирадикальної дії як вірогідного механізму актопротекції та оцінювання перспективності високоактивних сполук для дальшого поглибленого дослідження. Матеріали та методи. Актопротекторну активність для перспективних і невідомих 3’-R-спіро[циклоалкіл-1(2), (гетарил-3(4), 6’)-[1,2,4]триазино[2,3-c]хіназолін]-2’(7’H)-2-онів вивчено за тестом плавальної проби при температурі 24–26 °C (нормотермія) з додатковим навантаженням (10 % від маси тіла експериментальних тварин). Дослідження здійснили на білих щурах лінії Вістар, як референс-препарат використаний «Мілдронат». Результати. Встановили, що більшість протестованих сполук при внутрішньошлунковому введенні у дозі 50 мг/кг збільшують тривалість плавання експериментальних тварин в умовах нормотермії. Виявлений ряд високоактивних сполук (1.6, 1.11, 1.12, 1.18, 1.19, 1.25), що за рівнем актопротекторної активності перевищують референс-препарат «Мілдронат» на 13,2–47,8 %. Показано, що вірогідної залежності між актопротекторною та антирадикальною активністю серед 3’-R-cпіро[циклоалкіл-1(2), (гетарил-3(4), 6’)-[1,2,4]триазино[2,3-c]хіназолін]-2’(7’H)-2-онів немає. Аналіз взаємозв’язку «структура – активність» показав: критичними факторами у прояві високої актопротекторної дії є не тільки розмір і природа спіроциклу положення 6, а також замісник положення 3 триазино[2,3-c]хіназолінової системи. Найактивніші сполуки 1.6, 1.11, 1.12, 1.18, 1.19 та 1.25 рекомендовані для подальших фармакологічних досліджень.
3’-R-Спіро[циклоалкіл-1(2), (гетарил-3(4), 6’-[1,2,4]триазино[2,3-c]хіназолін]- 2’(7’H)-2-они – перспективний клас сполук з актопротекторною активністю
Keywords: 3’-R-spiro[cycloalkyl- 1(2), (hetaryl-3(4); 6’-1,2,4]triazino [2,3-c]quinazoline]- 2’(7’H)-2-оnes; swimming test; normothermia; actoprotective and antiradical activities; 3’-R-cпіро [циклоалкіл-1(2), (гетарил-3(4); 6’-[1,2,4]триазино[2,3-c]хіназолін]-2’(7’H)-2-они; плавальний тест; нормотермія; актопротекторна та антирадикальна активність